Unfolding the lesbianism orientation development amongst selected pengkid Malays - Rusdie Ali Faeidz, Nora Hendon Faeizah (2011)
Pengkid’, a Malaysian slang to describe women who have the appearance, mannerism and sexual orientation similar to men has been seen as a social ill and has raised many issues. This phenomenon challenges Malaysian’s stand as a Muslim country as it deviates from the traditional human orientation. The main purpose of this study was to unfold the contributing elements that may have contributed toward the lesbianism orientation development amongst the selected Malay ‘Pengkids’ in Malaysia in order to provide a new body of knowledge toward community education and development. The qualitative research methodology was selected since it was deemed the most appropriate for the study of this nature of phenomenon. The findings suggested that the lesbianism orientation of the Malay ‘Pengkids’ were developed throughout the different stage of their lives, childhood, adolescence and young adulthood and were contributed by two distinctive elements: the biological characteristics which were mainly based on the body built/structure, facial appearances and features of the Malay ‘Pengkids’; the social psychological and psychosocial process of the Malay ‘Pengkids’ life developments. The study mainly concluded that the early stage of childhood development is deemed to be very important in the formation of one’s gender/sexual identity development and parents are the most important agent to nurture children on healthy gender/sexual orientation development.